已知[-3x的m+1次方乘y²]³÷[-2x³乘y的n+1次方]²=-4分之81 x³

来源:学生作业帮助网 编辑:作业帮 时间:2024/09/29 16:02:46
已知[-3x的m+1次方乘y²]³÷[-2x³乘y的n+1次方]²=-4分之81 x³
x){}Ku+j6|fi;Qlhna ,o5A@y0ű&O;ڞ0TI*ҧ v6ţ42^ٜN@qƹƚqf@L**44cmqV}Mn]n ]{9/uzѼi㬧^GzYӳyso~o'Џz=`dX?@3FGm@"OvL <_tt\[#<[#<;P

已知[-3x的m+1次方乘y²]³÷[-2x³乘y的n+1次方]²=-4分之81 x³
已知[-3x的m+1次方乘y²]³÷[-2x³乘y的n+1次方]²=-4分之81 x³

已知[-3x的m+1次方乘y²]³÷[-2x³乘y的n+1次方]²=-4分之81 x³
∵[-3x的m+1次方乘y²]³÷[-2x³乘y的n+1次方]²=-4分之81 x³,有
[-27x^(3m+3)y^6]÷[4x^6y^(2n+2)]==-4分之81 x³
(-27/4)x^(3m-3)y^(4-2n)=-81x²/4
x^(3m-6)y^(4-2n)=3
因为题目有问题,只能做到这里.
如果右边的81换成27的话;有:
x^(3m-6)y^(4-2n)=1→3m-6=0且4-2n=0可得:m=2,n=2